2019
DOI: 10.4236/ajps.2019.101010
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying and Validating Soybean Seed Emergence Model as a Function of Temperature

Abstract: Developing a model for soybean seed emergence offers a tool producers could use for planting date options and in predicting seedling emergence. In this study, temperature effects on soybean seed emergence were quantified, modeled, and validated. The data for seed emergence model development was generated at varying temperatures, 20˚C/12˚C, 25˚C/17˚C, 30˚C/22˚C, 35˚C/27˚C, and 40˚C/32˚C, on two soybean cultivars, Asgrow AG5332 and Progeny P 5333 RY. Time for 50% emergence (t50%) was recorded, and seed emergence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…The optimal Tbase also differed by cultivars (Figure 3, Table 4). Similar results have been observed by Alsajri et al [31] after comparing the optimal base temperatures of two soybean cultivars. For Pungsan, Soweon, and Heapum, CVs increased as T base increased at stage from sowing to flowering.…”
Section: Determination Of Optimal Base Temperatures For All Six Soybean Sprout Cultivarssupporting
confidence: 90%
“…The optimal Tbase also differed by cultivars (Figure 3, Table 4). Similar results have been observed by Alsajri et al [31] after comparing the optimal base temperatures of two soybean cultivars. For Pungsan, Soweon, and Heapum, CVs increased as T base increased at stage from sowing to flowering.…”
Section: Determination Of Optimal Base Temperatures For All Six Soybean Sprout Cultivarssupporting
confidence: 90%
“…Normalized values were fit to a simplified beta function representing the relative response to the temperature of these four growth and development categories: shoot growth, and development and root growth and development (Figure 8). Understanding potential growth and development under optimal conditions is useful when optimizing crop simulation models [36] and when creating simple models for field application [37,38]. The potential growth and development values for each parameter in this study were derived from the modified beta functions fit to the data at each harvest shown in Figures 4-6.…”
Section: Discussionmentioning
confidence: 99%
“…The functional algorithms could estimate potential corn shoot and root growth parameters at any given location for any given sowing dates. Additionally, the algorithms could improve the existing corn models [36][37][38][39][40] in enhancing their functionality. Both simple and complex crop simulation models will have potential utilization in emerging precision agriculture technology [41].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The AEMs triggered soybean sowing each season between 15 March and 15 May when air temperature exceeded 9°C (7 days moving average) and soil temperature exceeded 7°C (5 days moving average). This is a one degree lower threshold, as known for later MGs (III–V; Alsajri et al, 2019), owing to the cold‐temperature adaptation of the earlier MGs (Ritter & Bykova, 2021). Harvest was triggered at simulated maturity.…”
Section: Methodsmentioning
confidence: 77%